RELATIONSHIP BETWEEN EARLY CHILDHOOD EDUCATION AND FAMILY: IN SEARCH OF A WELCOMES EDUCATION - Mantovani Leite, Sandra Regina; Carvalho, Alonso Bezerra de [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2018)
The purpose of this paper is to present considerations about the importance of the relationship family institution and early childhood institution, in order to provide the child a cozy education. An education that will be realized with shares of care and care, affection and caring, family and school assuming their responsibilities and acting in an integrated manner. Therefore also will point out the inseparability of care and education, as a way of enhancing actions that favor human interaction. Thus, this paper aims to provide time for reflection for all those involved in the educational practice, presenting options, concerns, questions and aspirations for education to become more human for the child. We believe that the practices carried out in a warm environment where children, their families and teachers have voice and time, with opportunities to share experiences and ideas transform the school into a humanizing space.
Keywords: Child education; Family; Child; Care